1957
DOI: 10.1071/zo9570013
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of the eggs of Mammalian Lice on their hosts. 1. Description of the Oviposition behaviour.

Abstract: The behaviour patterns of Damalinia ovis (L.), Linognathus stenopsis (Burm.), and Haematopinus eurysternus (Nitz.) were found to be similar and readily divisible into three stages. In the first stage the louse sought the warm end of a temperature gradient. There it entered upon the second stage in which it remained stationary for a variable period with its head pointed towards the warm end. In D. ovis there was marked abdominal movement. The third stage lasted only 3 or 4 min and culminated in the deposition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1974
1974
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Estudos realizados por Murray (1957aMurray ( ,b, 1963 na Austrália mostraram que existem vários fatores envolvidos na variação estacional de B. ovis, dentre estes, o excesso de precipitações pluviais são prejudiciais para estes malófagos, devido ao encharcamento do velo dos ovinos. Em condições experimentais Murray (1960) observou que umidades de 100% cessam o desenvolvimento dos ovos, a imersão em água por uma hora é letal para 50% dos ovos e o velo embebido em água causa morte em 75-100% de ninfas e adultos.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…Estudos realizados por Murray (1957aMurray ( ,b, 1963 na Austrália mostraram que existem vários fatores envolvidos na variação estacional de B. ovis, dentre estes, o excesso de precipitações pluviais são prejudiciais para estes malófagos, devido ao encharcamento do velo dos ovinos. Em condições experimentais Murray (1960) observou que umidades de 100% cessam o desenvolvimento dos ovos, a imersão em água por uma hora é letal para 50% dos ovos e o velo embebido em água causa morte em 75-100% de ninfas e adultos.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…It is possible that a similar lock-and-key relationship exists between the gonopods of lice (appendages used to clasp hairs while attaching eggs) and hair diameter of their hosts (Murray, 1957(Murray, ,1987. For example, Murray (1957) showed experimentally that lice would not lay eggs unless they could grasp the hair securely between their abdomen and gonopods.…”
Section: Discussionmentioning
confidence: 99%
“…Murray (1960Murray ( , 1968 has reported that atmospheric temperature, shearing, solar radiation and thunderstorms are responsible for the summer decline in the population of sheep louse, Bovicola ovis. Furthermore, the shedding of winter coat and higher temperature in summer play critical role in reducing the number of B. equi on horses (Murray 1957(Murray , 1963. The infestation intensity of Tricholipurus parallelus on white tailed knock down in summer due to moulting, higher summer temperature and thunderstorms (Samuel and Trainer 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Thorough look on literature have revealed that study on avian lice population response to seasonality have been documented by Boyd (1951), Woodman and Dicke (1954), Ash (1960), Touleshkov (1965), Baum (1968), Foster (1969), Eveleigh and Threlfall (1976), Agarwal and Saxena (1979) and Chandra et al (1988Chandra et al ( , 1990. Furthermore, seasonal changes in mammalian phthirapteran have been studied by Craufurd-Benson (1941), Matthysse (1946), Cowan (1946), Scott (1952), Allen and Dicke (1954), Murray (1957Murray ( , 1960Murray ( , 1963Murray ( , 1968, Anderson (1962), Murray and Gordon (1969), Samuel and Trainer (1971), Amin and Madbouly (1973), Rust (1974), Saxena (1990, 1992) and Kumar et al (1993). A majority of above workers have noted that mammalian lice are generally exhibited peak intensity of infestation in the winter months while the avian lice are found maximum in the summer months.…”
Section: Introductionmentioning
confidence: 99%